2013
DOI: 10.1177/0022034513484330
|View full text |Cite
|
Sign up to set email alerts
|

Computerized Dental Injection Fear Treatment

Abstract: One in four adults reports a clinically significant fear of dental injections, leading many to avoid dental care. While systematic desensiti-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 15 publications
0
28
0
2
Order By: Relevance
“…110,111 Individuals view a series of video segments in which a fearful patient is taught coping skills (including diaphragmatic breathing and progressive muscle relaxation, as described above) and then taken through the gradual steps of a dental injection. In a randomized clinical trial, individuals completing the CARL programme showed greater fear reduction than individuals receiving an informational pamphlet about dental injections, 112 and fearful patients have found CARL to be an acceptable way to reduce their dental injection fear. 113 Whether done in person or via computer, systematic desensitization allows patients to learn to reduce their anxiety while taking 'baby steps' through procedures.…”
Section: Systematic Desensitizationmentioning
confidence: 99%
“…110,111 Individuals view a series of video segments in which a fearful patient is taught coping skills (including diaphragmatic breathing and progressive muscle relaxation, as described above) and then taken through the gradual steps of a dental injection. In a randomized clinical trial, individuals completing the CARL programme showed greater fear reduction than individuals receiving an informational pamphlet about dental injections, 112 and fearful patients have found CARL to be an acceptable way to reduce their dental injection fear. 113 Whether done in person or via computer, systematic desensitization allows patients to learn to reduce their anxiety while taking 'baby steps' through procedures.…”
Section: Systematic Desensitizationmentioning
confidence: 99%
“…As an example, a recently published RCT examined a self-paced computerized cognitive-behavioral intervention based on systematic desensitization for dental injection phobia. 8 This study found that while this intervention did not have a significant effect on how many patients received an optional dental injection, it did significantly decrease self-reported dental anxiety. Unlike many of the studies reviewed in the current meta-analysis, this paper followed the CONSORT checklist, including all of the necessary components that Wide Boman and colleagues 1 were unable to report on in the papers reviewed.…”
Section: Commentary and Analysismentioning
confidence: 73%
“…The fear concerning the pain from the anesthetic injection is very frequent (2) and these patients could report greater pain during the anesthetic act compared to patients without fear (16). We selected the upper third molar removal as a model to our study because it is a very reproducible model of surgical intervention.…”
Section: Discussionmentioning
confidence: 99%